DEVELOPING ACTIVITIES, INDEPENDENCE AND ASPECTS OF MOTORIK HALUS USING THE EXTREAM MODEL IN GROUP B2 CHILDREN - hairunnisa hairunnisa; Celia Cinantya (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2022)
AbstractThis studyaims to describe teacher activities and analyze activities, independence and fine motor aspects of children. The problem in this i researchis the low activity, independence and motor aspects ofchildren. This is due to the lack of meaningful learning, children lack opportunities in independent learning activities, and lack of activities that train children's fine motor skills. An attempt to solve this problem is to use the EXTREAM model (E Xplicit insTRuction, kolasE and mediA alaM materials). This research approach uses a qualitative approach with a type of classroom action research (PTK), the subject of research in group B2 children in Aisyiyah Bustanul Athfal 15 Banjarma sin Kindergarten. Data collection techniques use observation sheets on teacher activities, children's activities, independence and fine motor aspects. Meanwhile, data analysis is the analysis of descriptions and cross tables and achievements and criteria. The results showed that teacher activity achieved very good criteria at meeting 3. The child's activity at meeting 3 reaches the criteria of